Layanan Corner di Perpustakaan Universitas Andalas - Sari, Elviza Agustina; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2016)
Service corner at Andalas University Library has three objectives. First, to describe the service corner at Andalas University Library. Second, to determine the constraints that exist in each service corner at Andalas University Library. Third, to look for efforts to be made to overcome the obstacles that are in service corner at Andalas University Library. Data were collected through direct observation and interviews. The research sample was the librarian at each corner of existing services. Data analysis techniques used are qualitative and quantitative techniques. Data obtained from the study were analyzed by using the relevant literature, both from source books, and the Internet in accordance with the topic. Based on data analysis we can conclude three things, namely (1) the service corner available in the Library of the University of Andalas has four types of services such as the American corner, Minangkabau corner, French corner, and Bank Indonesia corner, (2) the service corner available in the University Library Andalas has three constraints include lack of visitors, recording books are still manual, funding the collection are hung and the collection is still limited, (3) the efforts made to overcome the obstacles that are in service corner by way of sale, increase the use of more adequate facilities and conduct business more zealous to obtain funding seamlessly.Â Keyword: service corner, academic library